Synthesis and characterization of biomimetic of Zinc Oxide - Nur Aziah Abdul Rahim (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
The scope of this project is to synthesize the biomimetic ZnO by using biological template which is tunza pine and peppermint. Besides, the characterization of the synthesized zinc oxide will be characterized by using scanning electron microscopy (SEM), X-Ray Powder Diffraction (XRD) and Brunauer Emmett Teller (BET). Lastly, the photocatalytic activity of the synthesized ZnO will be studied through photoreduction of Fe3+ under solar light irradiation.